Experimental Investigation of the Carrying Capacity of an Ice Cover (Eksperimentalnye Issledovaniya Gruzopodbemnosti Ledyanogo Pokrova) - Panfilov,D. F. (1972)
In the report, the author discusses an experimental method permitting one to determine the carrying capacity of an ice cover with adequate accuracy and with minor expenditures of time and resources. Results are given from tests conducted by the author under field and laboratory conditions. Draft trans. of Vsesoyuznyi Nauchno-Issledovatelskii Institut Gidrotekhniki. Izvestiya (USSR) v64 p101-115 1960.